Within-individual variation in sexual displays: signal or noise?. (7th December 2018) - Tanner, Jessie C; Bee, Mark A
Abstract : Male sexual displays are variable within individuals, but we know very little about how this variation in signal production affects animal communication. Within-individual variation does not appear to signal male quality as a potential mate and may simply obscure mean male trait values. Female treefrogs nevertheless prefer males who produce consistent signals of male quality but may not be able to express this preference in dense breeding aggregations, which produce high levels of chorus noise. Abstract: Animal sexual displays are typically repeated over time and consist of components that are also repeated within a display, creating potential for within-individual variation in signal production. Across taxa, patterns of variation in and female preferences for temporal properties of signals are well documented, but data describing how within-individual variation functions in communication are scarce. Is within-individual variation itself a signal of male quality, or noise that obscures another signal encoded by a temporal pattern? In this study of Cope's gray treefrog, Hyla chrysoscelis, we used synthetic advertisement calls to examine the function of within-individual variation in two signal traits: pulse rate, a signal of species identity, and call rate, a signal of male quality. We examined relationships between male body condition and coefficients of variation within males for both signal traits. We then measured female preferences for within-individual variation. Because treefrogs communicate in noisy social aggregations, we repeated the experiment in quiet and at three amplitudes of chorus-shaped noise to evaluate how within-individual variation affects mate choice in natural settings. Within-individual variation in signal production was not predicted by male condition and likely acts as noise in this communication system. Females strongly discriminated against highly variable call rates, but not pulse rates, when the mean trait values of signals were taken into account. At its highest level, chorus noise abolished this effect, suggesting female preferences against within-individual variation are unlikely to be expressed in dense social aggregations.